Analyzing Results from Agricultural Large-scale Economic Simulation Models: Recent Progress and the Way Ahead - Wolfgang Britz; Ignacio Peŕez-Dominguez; Gopalakrishnan Badri Narayanan (German Journal of Agricultural Economics (GJAE), 2015)
This article discusses the role of post model pro-cessing and Graphical User Interfaces (GUIs) in the context of applying large and complex economic simulation models for Impact Assessment (IA) of policies impacting the agricultural and food sectors. The calculation of indicators from different domains and decomposition approaches is presented as part of post-processing of model results. We review user roles with regard to the application of complex economic models in agricultural IA, concluding that the GUIs will be mostly used by experienced analysts. The article stresses the role of GUIs in separating the code implementation of the economic model from the presentation of their results for analytical purposes. It highlights core functionalities of GUIs based on a detailed comparison between the GUIs and post-model analysis tools of three large economic models: Aglink-Cosimo, CAPRI and GTAP (Global Trade Analysis Project). Whereas the Aglink-Cosimo and CAPRI (Common Agricultural Policy Regionalised Impact Modelling System) models follow a strict separation between model and data analysis software tools, the GTAP model follows a model integrated approach using GEMPACK (General Equilibrium Modelling Package) tools. Moreover, the CAPRI GUI is technically and formally detached from the data generation process. Aglink-Cosimo and GTAP models use tools specifically developed to serve mainly their own needs (and tailored to communicate with their model drivers). One specific characteristic of Aglink-Cosimo relates to the need of interactive documentation for users due to the declarative nature of the code, which relies upon the obligation of the OECD and FAO to deliver a transparent and well-documented model and data-base to a formalized group of users. The CAPRI and GTAP models are much more research-driven and therefore have invested more resources in building bridges with other model consortia. We conclude that an integrated GUI would benefit from combining the best features of the different approaches presented.
Keywords: 330